A Keynesian system with microeconomic foundation. Microeconomics approach to the real sector in the Keynesian theory. - Rufasto A., Augusto (Universidad del Pacífico, 1997)
Incomes that are received by economic agents by means of selling part of their stocks in commodities, raw materials and production factors may be kept inside the domestic economic system or allowed to get away from it. The present article will show how in a system that is built over some definite decreasing (or at least non increasing) marginal productivity production functions, exogenous stimulus that might generate some demanding on final consumption goods, altogether with the consideration of a limit in household monetary spending in domestic final products, conduct to the shaping of one certain mathematical expression that is to connect gross domestic value with the above mentioned stimulus.   In a second stage, diverse applications and extensions of the model are performed, in order to discuss some interesting subjects in economic theory.